Biogas production from sewage sludge as a distributed energy generation element: Anationwide case study for Turkey - (:unkn) unknown (My University, 2019)
Sewage sludge is outcome of the wastewater treatment process. It contains hazardous biological and chemicalcompounds that need to be stabilized. Anaerobic digestion is among the stabilization methods of sewage sludge.Digestion process destroys organic fraction of sewage sludge and produces biogas (%65 Methane, %34 CO2 and etc.).Biogas is burned in internal combustion engines to produce electricity. Digested residue can be used fertilizer. In thisstudy, the total electricity production that can be obtained by anaerobic digestion of all wastewater treatment plantsthroughout the country is examined. Main objective of this study is preliminary evaluation of energy potential ofbiogas from sewage sludge anaerobic digestion. Since Wastewater Treatment Plants are distributed in the variousregions of a city, above mentioned biogas plants should be considered as distributed generation equipment. Use ofsmall scale energy production plants near the consumers is called distributed generation. Energy transmission lossesand related infrastructure cost can be reduced or delayed by means of distributed generation. Within a smart gridapproach, mentioned plants can support electricity grid. They can also serve as local emergency power plants. As anationwide scenario WWTP are evaluated. Biogas energy capacity potential of 234 plants is calculated. Capacities lessthan 100 kWe are assumed to be non-feasible due to scale economy. It is evident that 91 plants can be installed withan average capacity of 660 kWe.